Insight into the adverse effect of residual ammonium ion on the catalytic activity of zeolite Y - Azam Samiei; Seyyed Hamid Ahmadi; Amir Bagheri Garmarudi; Mahta Badienejad; Miguel de la Guardia; Daniel Gallert Mateu (Results in Chemistry)
Zeolite Y is a solid acidic catalyst with a high surface area and accessible active sites and it is widely used in petrochemical processes. To generate Brønsted acid sites, NaY must be converted to the H-form, producing OH groups. Converting NaY to the HY zeolite with ammonium ions can leave ammonium in the zeolite cages. Residual ammonium ions, which have not been extensively considered, can affect the textural properties and catalytic performance of the zeolite. The quantification of ammonium ions can help control the time and temperature of calcination, thereby enhancing the catalyst efficiency. ATR-FT-IR spectroscopy, with the band intensity at 1450 cm−1 that is linearly dependent on ammonium content, was used for the quantitative measurement of residual ammonium in zeolite cavities. XRD, XRF, N2 adsorption/desorption, CHNS, and NH3 TPD have been used to evaluate physicochemical properties and acid site behaviors. The catalytic performance for the conversion of kerosene was investigated using a fixed bed reactor followed by GC–MS spectroscopy. The results evidenced that the increase of the ammonium ions within the structure of zeolite enhanced the cracking of kerosene. However, the coke content, considered an undesirable factor in the catalytic cracking process and capable of reducing catalyst lifetime, exhibited an increasing trend with higher ammonium content. Since the remaining ammonium ions block the micropores or micropore entrances, the specific surface area and pore volume are reduced.